(untitled) - Zenger, John H. (New York, 2009)
The Inspiring Leader reveals the authors’ newest proprietary research on how top leaders inspire teams to greatness. It discusses the behaviors exhibited by the most successful leaders and includes advice on how to implement them. Drawing from statistically significant data and objective empirical evidence, the book shows how to: * Establish a clear vision and direction; * Use the power of emotions; * Create stretch goals for your team; * Foster innovation and risk taking; * Encourage teamwork and collaboration; * Champion change, and much more
Keywords: Leadership,Employee motivation,Khả năng lãnh đạo,Thăng tiến công việc